School Based Management Within The Framework of Autonomy at SMP Negeri 1 Rejang Lebong - Hamengkubuwono Hamengkubuwono (Institut Agama Islam Negeri (IAIN) Curup, 2021)
School-based management is an educational management concept that provides autonomy for a school in organizing the continuity of education according to the needs of the school context. By applying a case study, this study was conducted to reveal the implementation of school-based management, along with its supporting and inhibiting factors, at SMP Negeri 1 Rejang Lebong, Curup, Bengkulu. All potential parties at school that could provide the expected data were involved purposively as the subjects. Data garnered from them were solicited using interviews and observations, which were then triangulated and analyzed using an interactive model. The interactive model worked in four components, namely data collection, data condensation, data presentation, and drawing a conclusion. The findings showed that SMP Negeri 1 had implemented school-based management functions properly, including planning, organizing, implementing and supervising the aspects of human resource management, student management, facilities and infrastructure management, financial management, curriculum and learning management, and management of school and community relations. Supporting factors for the implementation of school-based management included the participation of committees, parents, community at school, complete teaching staff, facilities and infrastructure. Meanwhile, the inhibiting factor was that some students still did not obey the school rules.